Correlation of Leg Length and Leg Muscle Strength with Kicking Ability in Pencak Silat Sports - Suyudi, Imam (Sains Global Institut, Indonesia, 2023)
This research is descriptive research with a correlational design. This study aims to determine: the relationship between leg length and muscle strength with Kicksing ability in Pencak Silat sports. The population used was SMA Negeri 7 Makassar. The sample chosen in this research is representative and can represent the students of SMA Negeri 7 Makassar as a whole. The sample chosen was male students who actively participated in daily learning at school. Determination of the sample in this research was carried out in two stages, namely; (1) the first sample is to determine the class levels (cluster sampling) from previously determined schools, namely class X and class XI; and (2) the second stage of the sample is random sampling of male students at grade levels, by determining the number of students that will be used to obtain empirical data. The number of samples used in this research, with details that; (1) for class X students as many as 30 students; and (2) for class XI students as many as 30 students. So the total sample is 60 people. The sampling technique was carried out randomly (random sampling) so that a representative sample could be obtained that could represent the students of SMA Negeri 7 Makassar as a whole. The analysis technique used is regression and correlation analysis using the SPSS application program version 22.00 with a significance level of 0.05 α. The results of the research show that: (1) There is a significant relationship between leg length and Kicksing ability in Pencak Silat sports, with a value of r0 = 0.710; (2) There is a significant relationship between leg muscle strength and Kicksing ability in Pencak Silat sports, with a value of r0 = 0.854; and (3) There is a significant relationship between leg length and leg muscle strength with Kicksing ability in Pencak Silat sports, with a value of r0 = 0.859.